A CASE-CONTROL STUDY OF CHOROIDAL THICKNESS IN PATIENTS WITH CENTRAL SEROUS CHORIORETINOPATHY: A STUDY AT RIMS, RANCHI, JHARKHAND - Kumari, komal; Prasad, Rahul; Suman, Priya; Marshal, Nitish Kumar (Student’s Journal of Health Research Africa, 2025)
Background Central Serous Chorioretinopathy (CSCR) is a retinal disorder characterized by the accumulation of subretinal fluid, often linked to retinal pigment epithelium (RPE) dysfunction and choroidal hyperpermeability. Choroidal thickness, a key parameter in understanding the pathophysiology of CSCR, has been implicated in disease onset and progression. Despite extensive research, regional variations in CSCR and choroidal thickness remain underexplored, especially in Indian populations. Objectives: This study analyzed and compared choroidal thickness in patients with CSCR and healthy controls. It also sought to investigate the relationship between choroidal thickness and disease severity. Methods A 12-month case-control study was conducted at RIMS Ranchi from January 2024 to December 2024, Jharkhand. The study included 50 patients diagnosed with CSCR and 50 age—and sex-matched healthy controls. Choroidal thickness was measured using Optical Coherence Tomography (OCT) in the subfoveal region and 500 μm nasal and temporal to the fovea. Descriptive statistics were used for baseline data, while t-tests and correlation analyses assessed differences and relationships between choroidal thickness and clinical parameters. Results CSCR patients exhibited significantly greater mean subfoveal choroidal thickness than controls (p < 0.001). Similar differences were observed in the nasal and temporal regions. A positive correlation was noted between disease duration and choroidal thickness (r = 0.46, p = 0.001), while an inverse relationship was found between choroidal thickness and best-corrected visual acuity (BCVA) (r = -0.39, p = 0.005). These findings reinforce the role of choroidal thickening in CSCR pathophysiology and its association with disease progression. Conclusion This study highlights the clinical relevance of choroidal thickness as a diagnostic and prognostic marker in CSCR. The findings emphasize the importance of early detection and monitoring choroidal changes to improve management and outcomes. Recommendation Further longitudinal and multicenter studies are recommended to validate these observations and explore therapeutic implications.